Gender inequality in metal music production - Berkers, Pauwke; Schaap, Julian (Bingley, U.K. : Emerald Publishing Limited, 2018)
For over four decades, scholars have been investigating male dominance - both symbolically and numerically -within popular music. The heavier genres of popular music, metal music in particular, have been male dominated spaces, which are difficult to navigate for women participating as fans, musicians, or both. Studies on gender inequality in metal music have convincingly demonstrated how gender dynamics shape the reception of metal music and metal scenes all over the globe. Yet, they shed relatively little light on the extent of and reasons for metal music's male domination from a production perspective. This book fills this gap, offering is a systematic and large-scale overview of gender inequality in metal music production. In other words: how many women - compared to men - are participating in metal bands and what are the causes for the differences in participation?
Includes index.
Includes bibliographical references.
Print version record
Keywords: Mass media and sex; Heavy metal (Music); Social Science -- Gender Studies; Gender studies: women